Thermo-electrochemical generation capabilities of octahedral spin crossover complexes of Mn(II), Fe(II) and Co(II) with N-donor ligands and benzoate counter ion. (20th January 2018) - Hasnan, M. M. I. Megat; Abdullah, N.; Said, S.M.; Salleh, M. F. Mohd; Hussin, S. A. Mat; Shah, N. Mohamed
Abstract: Spin crossover ionic complexes have shown potential as efficient thermoelectrochemical materials which are capable of converting electrochemical energy into electrical potential in the presence of a temperature gradient. In this work, we have measured the Seebeck coefficient, ionic conductivity and the electrical power output of three proposed spin crossover ionic complexes. These three complexes are [Mn(cyclam)(L)2 ] 2+, [Co(cyclam)(L)2 ] 2+ and [Fe(cyclam)(L)2 ] 2+ with transition metal core, N-donor ligands and benzoate counter ion. It was found that the Seebeck coefficients and ionic conductivities of the proposed ionic complexes are highly dependent on the choice of transition metal. This dependency is expected to be most likely due to the selective agglomeration formed by the complexes through the Jahn-Teller effect of the ionic complexes. The ionic conductivity of these ionic complexes with KI-KI3 in presence of TBATFB without optimization were already three order magnitude higher than a control redox solution of KI-KI3 in the presence of low molarity of TBATFB. Consequently, this new perspective of agglomeration formation may provide a molecular design tool for synthesising spin crossover metal complexes for high performance thermo-electrochemical electricity generation. Graphical abstract: Image 1 Highlights: SCO materials possessing an octahedral structure as thermo-electrochemical cells material. Increase ionic conductivity and Seebeck coefficient for thermo-electrochemical cells (TECs) applications. Low molarity of TECs material.